The Influence of Discipline on Employee Work Productivity - Dwi Rani Fauziah; Anisah, Anisah; Hanif Al Kadri; Hendri Budi Utama (Journal of Educational Management Research, 2025)
This research is motivated by the phenomenon that shows that there are still employees whose work productivity and discipline are not optimal in carrying out their duties and responsibilities. The purpose of this study is to obtain data and information about work productivity, discipline and whether or not discipline influences employee work productivity in carrying out their duties in Educationoal Office. This study uses a quantitative method with a correlational approach. The population in this study was 90 people with a sample size of 73 people based on the Krejcie & Morgan Table taken using a proportional random sampling technique. The research instrument was a questionnaire with a Likert scale that has been tested for validity and reliability.The results of data analysis show that work productivity is in the good category with a TCR of 89%, discipline is in the good category with a TCR of 88%. There is a significant influence between discipline and work productivity with r count 0.588> r table 0.227 and t count = 6.218> t table = 1.992 at a significance level of 5% and an Adjusted R square of 0.337 or 33.7%. Based on the results of the study. The conclusion is that discipline is one of the factors that influence employee work productivity at the Batam City Education Office.